1975
DOI: 10.1021/bi00691a010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ornithine decarboxylase in 3T3 cells by putrescine and spermidine. Indirect evidence for translational control

Abstract: Addition of putrescine of spermidine prevents the increase in ornithine decarboxylase activity in cultures of 3T3 cells brought about by pituitary growth factors and results in a rapid, specific, and reversible reduction of enzyme activity in cultures previously stimulated by the growth factors. These effects are not due to polyamine toxicity and do not require other organic medium components. The amines apparently share a single carrier-mediated transport system in 3T3 cells. Methylglyoxal bis(guanylhydrazon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
50
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 41 publications
7
50
0
Order By: Relevance
“…In contrast to effects on SSAT activity, SPD and SPM sharply reduced ODC activity in CHX-pretreated cells by 6-7-fold. Down-regulation of ODC is not unexpected since it is one of the first recognized cellular events to be unequivocally attributed to exogenous polyamines [30,31]. Basically, two post-transcriptional mechanisms have been implicated: suppression of translation [5] and induction of a specific protein termed antizyme which binds to, inhibits, and contributes to the degradation of ODC (reviewed by Hayashi et al [6]).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to effects on SSAT activity, SPD and SPM sharply reduced ODC activity in CHX-pretreated cells by 6-7-fold. Down-regulation of ODC is not unexpected since it is one of the first recognized cellular events to be unequivocally attributed to exogenous polyamines [30,31]. Basically, two post-transcriptional mechanisms have been implicated: suppression of translation [5] and induction of a specific protein termed antizyme which binds to, inhibits, and contributes to the degradation of ODC (reviewed by Hayashi et al [6]).…”
Section: Discussionmentioning
confidence: 99%
“…The standard incubation mixture contained, in a final volume of 0.25 ml: 0.1 ml of cell extract; 25 tubes. After a 60-min incubation at 370, the reactions were halted by injecting 1 ml of 40% trichloroacetic acid through the rubber stopper.…”
mentioning
confidence: 99%
“…The mechanism whereby Bt2cAMP decreases the enzymatic activities in S49 cells is unknown. In other systems addition of putrescine blocks induction of ornithine decarboxylase (25)(26)(27)(28). In some, (26,28) but not all (27) cases, this inhibition is associated with the appearance of an intracellular inhibitor of the enzyme that has been termed an antizyme (28).…”
mentioning
confidence: 99%
“…It has been shown that exogenous polyamines are taken up and metabolized by cultured cells (Siimes & Janne, 1967;Clark & Fuller, 1975;Kremzner et al, 1975). A substantial increase in the intracellular polyamines is observed when extracellular concentrations rise to the endogenous concentrations (Clark & Fuller, 1975;Heller et al, 1978) and furthermore exogenous polyamines appear not to enter the same pool as amines synthesized within the cell (Russell et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial increase in the intracellular polyamines is observed when extracellular concentrations rise to the endogenous concentrations (Clark & Fuller, 1975;Heller et al, 1978) and furthermore exogenous polyamines appear not to enter the same pool as amines synthesized within the cell (Russell et al, 1970). These findings, together with the observed sensitivity of most cells to exogenous polyamine in the presence of much higher endogenous concentrations (Mitchell et al, 1978;Heller et al, 1978), make it difficult at present to assess the reason for different effects on cyclic AMP of increasing concentrations ofexogenous polyamines.…”
Section: Discussionmentioning
confidence: 99%